Museum Communication: The Representation of Malaysia’s National Identity in Muzium Negara - Ahmad Shaharir, Shafinaz; Mohd Adnan, Hamedi (Kajian Malaysia, 2026)
National identity remains a widely debated topic among scholars and cultural heritage institutions, particularly in multi-ethic societies like Malaysia. Museums, as key cultural institutions, play a crucial role in shaping and communicating national identity through their permanent exhibitions. Specifically, it explores how these exhibitions communicate narratives of Malaysia’s ethnic diversity and the decisions involved in curating national history and heritage. Using a qualitative approach, this study draws on online interviews with nine experts in museum studies, communication, Malaysian history, and culture. The findings revealed three themes: (1) exhibitions function as a communication channel that shapes public understanding of national identity; (2) the representation of the dominant ethnic group is more pronounced in Muzium Negara, leading to concerns about inclusivity; and (3) the political influence plays a significant role in shaping national identity through museum narratives. It also offers a theoretical contribution by applying Social Representation Theory (SRT) to explain how national identity is constructed, institutionalised, and sometimes silenced through museum exhibitions in the Malaysian context. Future research should explore how visitors interpret and engage with these representations to further understand the museum’s role in shaping national identity.